An innovative unit operation of particle separation/classification by irradiating low‐frequency ultrasound into water. Issue 5 (10th December 2017) - Muramatsu, Hiroya; Saito, Takayuki
Abstract : By irradiating kHz‐band ultrasound, submillimeter‐ or millimeter‐size particles that were dispersed in water with dissolved gases flocculated into a spherically flocculated particle swarm (SFPS). Acoustic cavitation‐oriented bubbles caused by the irradiation played essential roles in the formation of the SFPS. Unprecedented and promising phenomena were observed: the particles were separated based on their diameters through the precise control of the ultrasound irradiation, and the SFPS was easily manipulated using a motion‐controlled stick. The relationship between the sound‐pressure profiles and the manipulable range of the SFPS is discussed; that is, the effectively manipulable range was limited by the sound‐pressure profile. By means of manipulation control, we demonstrate the particle classification by particle diameters. On the basis of these findings, an example of a practical application of this technique is proposed. © 2017 American Institute of Chemical Engineers AIChE J, 64: 1564–1572, 2018